The Vitality of Reality Distortion in Tim Burton’s The Nightmare Before Christmas - Kurniawati, Wiwin Anggraeni; Siadari, Yoshua Veron Handika Putra; Pasopati, Rommel Utungga; Andharu, Devito; Fadillah, Muhammad Reza Ishadi (STKIP PGRI Ponorogo Press, 2025)
This writing investigates about the distorted reality portrayed in the Tim Burton’s movie called The Nightmare Before Christmas. The film follows the misadventures of Jack Skellington, Halloweentown's beloved pumpkin king, who has become bored with the same annual routine of frightening people in the